2005
DOI: 10.1152/ajpheart.00690.2004
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate formation of erythrocytes in postcapillary venules

Abstract: The purpose of the present study was to obtain information on erythrocyte aggregate formation in vivo. The movements of erythrocytes in postcapillary venules of the rat spinotrapezius muscle at various flow rates were recorded with a high-speed video camera before and after infusion of dextran 500. To distinguish aggregates, the following criteria were used: 1) a fixed distance (4 m) between the center points of two adjacent cells, 2) lack of visible separation between the adjacent cells, and 3) movement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
61
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 35 publications
13
61
0
3
Order By: Relevance
“…Microcirculation has been successfully studied using optical microscopy in various animal models (e.g., rabbit or mouse ear, hamster or mouse dorsal skin-flap window or skin-fold chamber, or open cremaster muscle) [52][53][54][55]59,63,[70][71][72][73] . The use of these models for high-resolution imaging of individual flowing or static cells may be somewhat limited because of significant light scattering from surrounding tissue (e.g., skin or muscles) and/or the relatively deep location of vessels below the skin.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcirculation has been successfully studied using optical microscopy in various animal models (e.g., rabbit or mouse ear, hamster or mouse dorsal skin-flap window or skin-fold chamber, or open cremaster muscle) [52][53][54][55]59,63,[70][71][72][73] . The use of these models for high-resolution imaging of individual flowing or static cells may be somewhat limited because of significant light scattering from surrounding tissue (e.g., skin or muscles) and/or the relatively deep location of vessels below the skin.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The monitoring of single RBCs and their small aggregates has usually been performed in two modes: 1) in selected microvessels (small venules or capillaries) with slow flow using a frame rate of 20-30 frames per second (fps), or 2) using a short time-exposure mode (∼0.1-1 ms) by which only single images of fast-moving cells can be captured [56][57][58] . Only a few studies demonstrated relatively high-speed imaging for measuring flow velocity in the range of 750-2500 fps in blood flow, and approximately 500 fps in lymph flow [19,26,59] . Due to motion distortion, these speeds are not quite fast enough to image shape and subcellular structures of individual fast-moving cells.…”
Section: Introductionmentioning
confidence: 99%
“…Vital microscopy, mainly transmission microscopy, has produced images of single cells in selected superficial blood microvessels with reasonable spatial ($0.8-2 mm) and temporal (10 À3 s) resolution [Rosenbaum et al, 2002;Kim et al, 2005;Lipowsky, 2005]. However, to date, images of single cells in fast flow ($1-5 mm/s) are obtained during one short exposure only (i.e., no successive high-speed framing), while continuous imaging (i.e., successive framing) can be realized only in relatively slow flow (<0.1 mm/s).…”
Section: Flow Cytometry In Vivo With Fluorescent Detectionmentioning
confidence: 99%
“…In a recent study (11), we examined the aggregation process in postcapillary venules, which is the site in the venous network where it first appears. In that study, we showed that aggregation occurs in a localized region of the postcapillary venule, ϳ15-30 m from the vessel entrance.…”
mentioning
confidence: 99%